OPTIMALISASI MODEL PROBLEM BASED LEARNING DIPADU DENGAN TEAM GAME TOURNAMENT DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS VIII—J SMP NEGERI 8 KEDIRI - Alhusna, Elma; Ni’mah, Masrifatul; Imron Hamzah, M. Ali; Budi Rahaju, Endah; Wahyu, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to measure the improvement in student learning outcomes at SMP Negeri 8 Kediri through the integration of two learning models: Problem-Based Learning (PBL) and Team Games Tournament (TGT) in Mathematics education. This type of research is Classroom Action Research (CAR). The study consists of two learning cycles, including a pre-cycle, cycle 1, and cycle 2. The subjects of this research are 34 students of class VIII-J at SMP Negeri 8 Kediri. The data collection techniques used are observation and testing to measure student learning outcomes during the implementation of the PBL combined with TGT model. The results of the study show a significant increase in learning mastery from the pre-cycle to cycle 2 after applying the PBL and TGT combination. Learning outcomes increased in each given learning cycle, from 24% in the pre-cycle to 68% in cycle 1 and further increased to 94% in cycle 2. This increase indicates that the combination of the two learning models, PBL and TGT, is an optimal combination for improving mathematics learning outcomes for class VIII-J students at SMP Negeri 8 Kediri.